THE INFLUENCE OF THE MEDIA ON ELECTORAL DECISIONS: HOW FAR DOES THE POWER OF INFORMATION GO? (CIPEEX, 2025)
This paper aims to analyze the impact of the media on public opinion formation and voter decision-making during presidential elections, considering traditional media (television, radio, and print newspapers) and digital platforms. Based on a literature review, we sought to understand how media exposure, agenda selection, news coverage, political marketing strategies, and the dissemination of misinformation affect perceptions of candidates. We discuss the effects of agenda-setting and framing on political image construction and the boundaries between information, manipulation, and voter autonomy. The study also proposes a reflection on the role of the media as an opinion-forming agent or as a mirror of already established trends among the electorate. The growing influence of social media and engagement algorithms is also addressed, especially in light of the post-truth phenomenon. We conclude that, although voters have critical capacity, the media has a strong potential to direct and select content, directly impacting the course of the democratic process.
Keywords: Media; Elections; Public opinion; Disinformation; Political marketing